The Impacts of Short-Term NMN Supplementation on Serum Metabolism, Fecal Microbiota, and Telomere Length in Pre-Aging Phase - Niu, Kai-Min; Bao, Tongtong; Gao, Lumin; Ru, Meng; Li, Yumeng; Jiang, Liang; Ye, Changming; Wang, Shujin; Wu, Xin (Frontiers in Nutrition, 2021)
Aging is a natural process with concomitant changes in the gut microbiota and associate metabolomes. Beta-nicotinamide mononucleotide (NMN), an important NAD+ intermediate, has drawn increasing attention to retard the aging process. We probed the changes in fecal microbiota and metabolomes in the pre-aging male mice (C57BL/6, age: 16 months) following the oral short-term administration of NMN. Considering the telomere length as a molecular gauge for aging, we measured this in peripheral blood mononuclear cell (PBMC) of pre-aging mice and human volunteers (age: 45-60 years old). Notably, the NMN administration did not influence the body weight and feed intake significantly during the 40 days in pre-aging mice. Metabolomics suggested 266 up-regulated and 58 down-regulated serum metabolites. We identified 34 potential biomarkers linked with nicotinamide, purine, and proline metabolism pathways. NMN significantly reduced the fecal bacterial diversity (p < 0.05) with increased abundance of Helicobacter, Mucispirillum and Faecalibacterium, and lowered Akkermansia abundance associated with nicotinamide metabolism. We propose that this reshaped microbiota considerably lowered the predicated functions of aging with improved immune and cofactors/vitamin metabolism. Most notably, the telomere length of PBMC was significantly elongated in NMN-administered mice and humans. Taken together, these findings suggest that oral NMN supplementation in the pre-aging stage might be an effective strategy to retard aging. We recommend further studies to unravel the underlying molecular mechanisms and comprehensive clinical trials to validate the effects of NMN on aging.